Prevalence of Pseudoexfoliation Syndrome and Pseudoexfoliation Glaucoma in Upper Egypt - Farrag Abdelsattar N; Shazly Tarek A; Kamel Asmaa; Al-Hussaini Ashraf K (BMC Ophthalmology, 2011)
Abstract Background Pseudoexfoliation (PXF) is a recognized risk factor for developing cataract, glaucoma and lens dislocation. PXF is also associated with increased risk of complications during cataract surgery due to poor mydriasis and zonular weakness. The aim of this study is to report the prevalence of pseudoexfoliation among Upper Egyptians attending the ophthalmology clinic of Assiut University Hospital. Methodology A retrospective, chart review study conducted in the period from February 2002 to August 2009. A total of 7738 patients aged 40 years or older attending the general ophthalmic clinics were included in this study. A detailed evaluation including ophthalmic and general history, slit lamp biomicroscopy, intraocular pressure measurement, gonioscopy and dilated eye examination were performed. Patients with pseudoexfoliative material on the anterior lens surface and ⁄ or the pupillary margin in either or both eyes were labeled as having PXF. Results Out of the 7738 patients included, three hundred twenty (4.14%) subjects had PXF. Mean age of PXF group was 68.15 years (SD 8.16, range 40-92 years). PXF was bilateral in 82.2% of cases. It was significantly associated with cataract, glaucoma and hearing loss. Of the PXF patients, 65% had cataract, 30.3% had glaucoma and 8.1% had hearing loss. Conclusion Pseudoexfoliation appears to be a common disorder in older individuals in Upper Egypt.